2013
DOI: 10.1186/1472-6882-13-313
|View full text |Cite
|
Sign up to set email alerts
|

Novel angiotensin I-converting enzyme inhibitory peptides derived from an edible mushroom, Pleurotus cystidiosus O.K. Miller identified by LC-MS/MS

Abstract: BackgroundAngiotensin I-converting enzyme (ACE) inhibitors have been reported to reduce mortality in patients with hypertension. Compared to chemosynthetic drugs, ACE inhibitors derived from natural sources such as food proteins are believed to be safer for consumption and to have fewer adverse effects. Some edible mushrooms have been reported to significantly reduce blood pressure after oral administration. In addition, mushrooms are known to be rich in protein content. This makes them a potential source of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 38 publications
2
32
0
2
Order By: Relevance
“…Although qualitative screening of chemical compounds found in mushrooms have been conducted using different analytical techniques (Petrova et al, 2007;Kanagasabapathy et al, 2011;Lau et al, 2013;Mohd Jamil et al, 2013), our metabolite profile study of these three edible mushrooms was performed for the first time via UPLC-HRMS. Chromatograms for the positive modes of all mushroom extracts studied are compared in Figure 5.…”
Section: Metabolite Profiling Of Ps Pa and Aa As Analysed By Uplc-mentioning
confidence: 99%
“…Although qualitative screening of chemical compounds found in mushrooms have been conducted using different analytical techniques (Petrova et al, 2007;Kanagasabapathy et al, 2011;Lau et al, 2013;Mohd Jamil et al, 2013), our metabolite profile study of these three edible mushrooms was performed for the first time via UPLC-HRMS. Chromatograms for the positive modes of all mushroom extracts studied are compared in Figure 5.…”
Section: Metabolite Profiling Of Ps Pa and Aa As Analysed By Uplc-mentioning
confidence: 99%
“…Meanwhile, various methods were also developed for in silico proteolysis to analyze the potential cleavage sites of protein sequences, such as BIOPEP [10] and PeptideCutter [11], which can be utilized to in silico hydrolyze known protein sequences, discover novel oligopeptides, and illuminate the action mechanism of natural proteins. Compared to in vivo proteolysis, the accuracy of in silico proteolysis has been validated by multiple approaches, including liquid chromatograph-mass spectrometer (LC-MS) [10,12,13,14]. In silico proteolysis is widely used to analyze natural proteins and generate bioactive peptides from food and halobios, such as milk, meat, tilapia, sea cucumber and so on [15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the culinary qualities of fruiting bodies, P. cystidiosus has a high nutritional value (proteins, fibre, minerals and vitamins) and the content of biologically active substances with proven health-promoting properties. The biological activity of these mushrooms has been confirmed in several laboratory tests and clinical trials, which showed, among others, their antitumor, anti-inflammatory, antiallergic, antiatherosclerotic, antibacterial, antiviral, antifungal, immunomodulatory and hepatoprotective properties as well as lowering blood sugar levels and the effect of blood cholesterol This mushroom is low in calories due to the limited content of lipids (Manzi and Pizzoferrato, 2000;Wasser, 2002;Croan, 2004;Thekkuttuparambil and Kainoor, 2007;Karaman et al, 2010;Abdullah et al, 2012;Patel et al, 2012;Lau et al, 2013;Siwulski et al, 2014;Usami et al, 2014).…”
Section: Temperature Of Incubationmentioning
confidence: 99%
“…Earlier documentation states that oyster mushrooms can be grown on a variety of waste materials, such as: various types of straw and sawdust, cotton waste, chopped and corn stover, waste from the production of palm oil, tea leaves, chopped cocoa pods (Vilgalys et al, 1996;Croan, 2004;Lau et al, 2013;Usami et al, 2014). During the last few years, there has been a very dynamic development in the production of edible and medicinal mushrooms.…”
Section: Temperature Of Incubationmentioning
confidence: 99%
See 1 more Smart Citation